2015
DOI: 10.5005/jp-journals-10024-1643
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Evaluation of Different Root Canal Sealing Materials

Abstract: Aim:To evaluate the solubility of five different root canal sealers (AH Plus Jet, RealSeal SE, MTA Fillapex, Tubli-Seal, and Acroseal) in chloroform, eucalyptol and Endosolv-E solvents. Materials and methods:Ninety root canal sealer samples were prepared and then divided into three groups for immersion in a solvent for 2, 5 or 10 minutes. The mean values of the root canal sealers' dissolution in the solvents were obtained by the difference between the preimmersion original weight and the post-immersion weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…MEK and ethyl acetate showed the highest ability to dissolve AH Plus sealer after chloroform. EndoSolv E, although not specific for resin sealers, had some solubility effect, as already reported (6). Like in other studies (6,7,25,26), the effect of EndoSolv R, eucalyptol, orange oil, and xylene was null.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…MEK and ethyl acetate showed the highest ability to dissolve AH Plus sealer after chloroform. EndoSolv E, although not specific for resin sealers, had some solubility effect, as already reported (6). Like in other studies (6,7,25,26), the effect of EndoSolv R, eucalyptol, orange oil, and xylene was null.…”
Section: Discussionsupporting
confidence: 74%
“…This investigation revealed that chloroform was the most effective solvent regardless of immersion time and UA execution, thus confirming its efficacy as an endodontic solvent (6)(7)(8). Although some authors claim that chloroform can be safe when used in a careful and controlled manner (21,22), there is still some controversy about its use in dentistry.…”
Section: Discussionmentioning
confidence: 57%
“… 43 Furthermore, chloroform has been shown to have a superior ability over other solvents in dissolving canal sealing materials. 44 Chloroform did prove to be effective when used with BC Sealer as it increased the likelihood of regaining patency in these samples ( Table 1 ). However, we believe that it may be necessary to develop a solvent that has superior effect on bioceramic sealers to improve its retreatability.…”
Section: Discussionmentioning
confidence: 98%
“…The microleakage current values seen in the present study showed a long-term continuous increase, which is similar to previous observations. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%